Exercise-Induced Acute Bilateral Upper-Arm Compartment Syndrome. (20th September 2017) - Traub, Brian C.; Lane, Mark K.; Traub, Jeff A.
Abstract : We present a rare case of acute exercise-induced bilateral upper-arm compartment syndrome in a patient who, after a year-long hiatus from exercise, subjected his upper-extremities to the stress of over 100 pushups. The patient presented with severe pain of the bilateral biceps and triceps and complaints of dark urine. Decompressive fasciotomy was performed followed by an intensive care unit (ICU) stay for associated myoglobinuria secondary to rhabdomyolysis. The patient suffered no long-term sequelae as a result of his conditions and recovered full function of the bilateral upper-extremities. Albeit rare, acute exercise-induced compartment syndrome should be considered as a diagnosis following unaccustomed bouts of exercise.